Float observations of an anticyclonic eddy off Hokkaido. Issue 8 (20th August 2016) - Inoue, Ryuichiro; Faure, Vincent; Kouketsu, Shinya
Abstract: To clarify the formation process of the salinity minimum in the Kuroshio–Oyashio mixed water region and understand the mechanism of meridional heat transport between the subtropical and subpolar gyres, 16 profiling floats were deployed within a warm‐core anticyclonic eddy off Hokkaido from June 2012 to December 2013. Then, the evolution of an anticyclonic eddy was examined using time series of the water properties. The largest fluctuations in water properties were observed in April and May 2013, when the anticyclonic eddy first moved south to interact with a warm front, then back north. Salinity in the salinity minimum layer increased during the interaction. After the eddy detached from the frontal structure, low‐salinity water was again observed with small intrusive structures, which eventually converged to a smooth zigzag structure in the potential temperature‐salinity diagram, suggesting that both vertical mixing and vertical heaving played a role in the temporal changes observed after the eddy detached from the front. Since the salinity variation during the interaction event was about half the total salinity change during the whole experimental period, the interaction of an eddy with a front might be important for modifying the water properties of the eddy, and, therefore, for the meridional transport of heat and fresh water. Key Points: 16 floats were deployed within a warm‐core anticyclonic eddy from June 2012 to December 2013 The evolution of an anticyclonic eddy was examined by using time series of the water properties The interaction of an eddy with a front might be important for modifying the water properties of the eddy